2014
DOI: 10.1002/cytob.21166
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Flow Cytometric Screening of SAP and XIAP Expression Accurately Identifies Patients withSH2D1AandXIAP/BIRC4Mutations

Abstract: Clinical flow cytometric screening tests for SAP and XIAP deficiencies offer good sensitivity and specificity for detecting genetic mutations, and are characterized by high negative predictive values. We recommend these tests for patients suspected of having XLP1 or XLP2. © 2014 Clinical Cytometry Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…This sequence contains a glycine residue at position 188, whose germline mutation marks a causative molecular aberration of the X‐linked lymphoproliferative syndrome type 2 (XLP‐2), which features low or instable expression of XIAP and premature apoptosis of lymphocytes in response to different stimuli (Rigaud et al , ). Two respective mutations of XIAP at G188 have been described, G188E and G188R, which diminish XIAP expression levels in patient B cells (Marsh et al , ; Gifford et al , ). Indeed, we found that both mutations abolish binding of XIAP to USP9X, and both XIAP mutants demonstrate reduced stability in mitosis (Figs D and EV1C).…”
Section: Resultsmentioning
confidence: 99%
“…This sequence contains a glycine residue at position 188, whose germline mutation marks a causative molecular aberration of the X‐linked lymphoproliferative syndrome type 2 (XLP‐2), which features low or instable expression of XIAP and premature apoptosis of lymphocytes in response to different stimuli (Rigaud et al , ). Two respective mutations of XIAP at G188 have been described, G188E and G188R, which diminish XIAP expression levels in patient B cells (Marsh et al , ; Gifford et al , ). Indeed, we found that both mutations abolish binding of XIAP to USP9X, and both XIAP mutants demonstrate reduced stability in mitosis (Figs D and EV1C).…”
Section: Resultsmentioning
confidence: 99%
“…Flow cytometry can detect functional defects in signaling pathways of MDP among patients with XIAP deficiency. 53,54 Detection of antibodies against enterocytes can be useful in the diagnosis of autoimmune enteropathy, particularly among patients with IPEX syndrome. 52 Additional tests for other rare genetic defects may also help in the detection of subgroups of earlyonset IBD, but are usually only available at specialized laboratories, often as part of research projects.…”
Section: Differences Between Early and Late Onset Ibdmentioning
confidence: 99%
“…This approach has been shown to provide good sensitivity and specificity compared with genetic mutation evaluation, and it is characterized by high negative predictive value. The lack of intracellular perforin expression in NK cells is characteristic of familial hemophagocytic lymphohistiocytosis type 2 [26,27].…”
Section: Sap Xiap and Perforin Expression In Hemophagocytic Lymphohmentioning
confidence: 99%